EFFECTIVENESS OF THE IMPLEMENTATION OF COOPERATIVE LEARNING MODEL OF TAI-TPS TYPE BY SCIENTIFIC APPROACH IN MATHEMATICS LEARNING TO CLASS VIII OF SMPN 13 MAKASSAR - Sarwedy Sarwedy (Daya Matematis: Jurnal Inovasi Pendidikan Matematika, 2018)
The research aims to discover the effevtiveness of the implementation of cooperatife learning model type TAI-TPS with Scientific approach in Mathematics learning to class VIII students at SMPN 13 Makassar. The research was pre-experimental research which emplyoed One-Group Pretest Posttest Design. The research involved one experiment class, namely class VIII.2 which consisted of 36 students who were chosen by using Random Sampling technique. The chosen class was given the treatment, namely cooperative learning models type TAI-TPS with Scientific approach in Mathematics learning. The data were collected by using by using learning result test, observation sheet, and questionnaire sheet. The data were analyzed by using descriptive and inferential statistics analysis as well as effectiviness analysis.The results of the research that Mathematics learning results of class after the implementation of cooperative learning models type TAI-TPS with Scientific approach 83,00 and deviation standar 6,14. The students activities in mathematics learning are in active category and than the students responses on cooperative learning type TAI-TPS in positive category. Based on teh effectiveness in significan α=0,05 with T-test showing that implementation of cooperative learning type TAI-TPS model with Scientifik approach effective in mathematic learning at VIII.2 SMPN 13 Makassar